2013
DOI: 10.1007/s10113-013-0541-4
|View full text |Cite
|
Sign up to set email alerts
|

The shifting territorialities of the Rhone River’s transboundary governance: a historical analysis of the evolution of the functions, uses and spatiality of river basin governance

Abstract: The shi'ing territoriali/es of the Rhone River's transboundary governance A historical analysis of the evolu/on of the func/ons, uses and spa/ality of river basin governance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
0
16
0
3
Order By: Relevance
“…The latter builds on the analytical framework proposed for the project "GOUVRHONE, Governance of the Rhône River from Lake Léman to Lyon", led at the University of Geneva [27], which has been inspired by the Institutional Resource Regime framework [36,37] developed for an analysis of regulatory frameworks through public policies, property rights and the interlinkages between these two legal corpus.…”
Section: Developing the Trbna Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The latter builds on the analytical framework proposed for the project "GOUVRHONE, Governance of the Rhône River from Lake Léman to Lyon", led at the University of Geneva [27], which has been inspired by the Institutional Resource Regime framework [36,37] developed for an analysis of regulatory frameworks through public policies, property rights and the interlinkages between these two legal corpus.…”
Section: Developing the Trbna Methodologymentioning
confidence: 99%
“…It is therefore important to ensure that the management of shared water resources is both sustainable and coordinated across riparian countries, respecting international law. A case study on the Rhone demonstrated that increasing cooperation and involving a variety of actors in transboundary dialogue-principles of IWRM-do not guarantee, alone, a more coherent management of the river [27]. However, cooperation is also a necessary (although not sufficient) condition to maintain international relations, in turn necessary to establish agreements and share benefits "beyond the river" [28].…”
Section: Cooperation and Benefitsmentioning
confidence: 99%
“…This has led to a range of approaches ranging from agency-led basin initiatives in England and Wales, river basin agency-led efforts in France and the Netherlands, and a more collaborative structure in Germany (Moss, 2012;Newig and Koontz, 2014;Warner, 2007). Each country has faced its own set of implementation challenges, including complications from multi-level implementation, distrust of public agencies with less participatory traditions, and the complications of international boundaries (Bréthaut and Pflieger, 2013;Newig and Koontz, 2014;Warner, 2007).…”
Section: Europementioning
confidence: 99%
“…Major questions relate to whether the governance framework of the Rhône is adequately adaptable to cope with current and future stresses; what are the current tensions in the governance framework at different scales; what are the existing major challenges in relation to a disconnect between ecological and institutional boundaries; whether or not an integrative and adaptive approach is possible in a transboundary context without a framework agreement in place (Adger et al 2009;Bréthaut and Pflieger 2013;Hill and Engle 2013;Lebel et al 2010;Pahl-Wostl et al 2008). …”
Section: Interdisciplinary Insights Into Responding To Multiple Pressmentioning
confidence: 99%
“…Under changing climatic conditions, the relicensing process offers the chance to rethink the waterenergy nexus and the adaptation capacities of the system. Bréthaut and Pflieger (2013) focus on the transboundary management of the Rhône River. Authors show the difficulties in implementing collaboration when the governance system is comprised of such different types of actors, legal frameworks and institutional levels.…”
Section: The Rhône Basin: a Context Of Changesmentioning
confidence: 99%